Masculine Foreign Policy: Geopolitical Codes Interpretation of Donald Trump 2nd Term - Agastya Wardhana; Vanyadhita Iglian (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2025)
This study offers an alternative explanation of Donald Trump's foreign policies during his second presedential term through a feminist lens in International Relations. Using the concept of hegemonic masculinity as the main analytical framework, combined with the geopolitical codes framework Through a speech analysis of ten of Trump’s foreign policy speeches and remarks delivered between January 21 and September 30, 2025, the study dissects his discourse across five dimensions of geopolitical reasoning. The findings reveal that Trump’s foreign policy consistently enacts and reproduces the logic of hegemonic masculinity by privileging dominance, transactional loyalty, coercive strength, and uniteralism. In this configuration, statecraft is remasculinized: protection becomes synonymous with control, and diplomacy is subordinated to unilateral power.